Constructing and Characterizing Bacteriophage Libraries for Phage Therapy of Human Infections - Gibson, Shelley B.; Green, Sabrina I.; Liu, Carmen Gu; Salazar, Keiko C.; Clark, Justin R.; Terwilliger, Austen L.; Kaplan, Heidi B.; Maresso, Anthony W.; Trautner, Barbara W.; Ramig, Robert F. (Frontiers in Microbiology, 2019)
Phage therapy requires libraries of well characterized phages. Here we describe the generation of phage libraries for three target species: Escherichia coli, Pseudomonas aeruginosa and Enterobacter cloacae. The basic phage characteristics on the isolation host, sequence analysis, growth properties, and host range and virulence on a number of contemporary clinical isolates are presented. This information is required before phages can be added to a phage library for potential human use or sharing between laboratories for use in compassionate use protocols in humans under eIND (emergency investigational new drug). Clinical scenarios in which these phages can potentially be used are discussed. The phages presented here are currently being characterized in animal models and are available for eINDs.